Quality of Primary Health Care models for brazilian children (Research, Society and Development, 2021)
Aim. To evaluate the quality of Primary Health Care (PHC) models for Brazilian children. Methods. A cross-sectional study was performed with 516 parents or guardian of children in the public preschools from a city in São Paulo State, Brazil. The participants completed the questionnaires on the perception of the quality of the PHC (Primary Care Assessment Tool-PCATool), and the socioeconomic conditions in their families. The data were analyzed by statistical tests (95% confidence level). Results. Private services, Family Health Strategies (FHS), and Conventional Health Care (CHC) were the modalities of PHC used by children. Among the three modalities, in all groups were observed statistically significant differences (p